Elevated plasma levels of endothelin are associated with the severity of sepsis and presence of shock in contrast to the levels of atrial natriuretic peptide - A. Beishuizen; J. M. Götz; L. Kip; C. Haanen; I. Vermes (Mediators of Inflammation)
Immunoreactive endothelin (ETi) and atrial natriuretic peptide (ANPi) blood levels were measured by radioimmunoassay in patients with clinically defined sepsis. The interaction between these two peptides and their relation to circulatory shock and mortality were studied. All septic patients (n = 16) had significantly higher ETi (22.3 ± 11.1 pg/ml) and ANPi (398.3 ± 154.3 pg/ml) plasma concentrations compared to control subjects (ETi, 4.1 ± 1.2; ANPi, 59.1 ± 14.8 pg/ml; n = 13). ETi levels followed the severity of illness according to the APACHE II scoring system and were higher in patients who did not survive. ETi levels were significantly higher in the presence of shock and bacteraemia. Furthermore, ETi correlated well with plasma lactate (r = 0.83, p < 0.05), but not with renal function. ANPi levels did not show correlation with any of these determinants. Serial blood sampling, six consecutive days after admission, showed that ETi levels gradually decreased in normotensive patients in contrast to patients with septic shock. ANPi levels did not show systematic changes in time, and no relationship was observed between ETi and ANPi levels. These results suggest that plasma ETi levels are indicative for disease severity and might have prognostic significance. The role of ANPi during sepsis remains to be eludicated.